Project Report on Design and Fabrication of Vertical Centrifugal Casting Machine and Evaluation of Aluminium Silicon Alloy - GURURAJ G, KIRUBAKARNA S, KATHIRAVAN and SRIRAM T S (1991)
INTERNAL GUIDE: CHANDRASEKHAR M, MVJCE
Keywords: Aluminium Silicon Alloy